2014
DOI: 10.1016/j.annemergmed.2014.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Provider Experience on Clinician-Performed Ultrasonography for Hydronephrosis in Patients With Suspected Renal Colic

Abstract: Overall, ultrasonography performed by emergency clinicians was moderately sensitive and specific for detection of hydronephrosis as seen on CT in patients with suspected renal colic. However, presence or absence of hydronephrosis as determined by emergency physicians with fellowship training in ultrasonography yielded more definitive test results. For clinicians without fellowship training, there was no significant difference between groups in the predictive accuracy of the application according to experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 18 publications
4
57
0
3
Order By: Relevance
“…A previous publication details the performance characteristics of PLUS by practitioners of different levels at our institution, many of whom participated in this study. 10 Our institution has an active point-ofcare ultrasonography program, including an emergency ultrasonography fellowship, as well as training requirements for residents that meet or exceed American College of Emergency Physician guidelines. 14 …”
Section: Methods Of Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous publication details the performance characteristics of PLUS by practitioners of different levels at our institution, many of whom participated in this study. 10 Our institution has an active point-ofcare ultrasonography program, including an emergency ultrasonography fellowship, as well as training requirements for residents that meet or exceed American College of Emergency Physician guidelines. 14 …”
Section: Methods Of Measurementmentioning
confidence: 99%
“…Previous work from our group has shown that emergency physicians with fellowship training in ultrasonography are better at accurately discerning hydronephrosis, and addition of PLUS by this group may provide more benefit than addition of ultrasonography by nonfellowship-trained emergency physicians. 10 Although all of the patients in our study received both ultrasonography and a CT scan, patients were eligible for inclusion only if the provider intended to order CT for suspected renal colic. Thus, some patients with symptomatic stones may not have been included if they were discharged without CT imaging.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 Point-of-care US represents an increasingly available imaging modality that may be used to reduce unnecessary CT scanning, although it is a user-dependent technology. 53,54 A recently published clinical prediction rule for ureteral stone, the "STONE score," incorporates sex and may be an effective way to predict ureteral stone without imaging, or to select patients who are more appropriate for reduced dose CT. 55 Research Question.…”
Section: Can a Protocol Which Takes Into Account Factors Suchmentioning
confidence: 99%
“…Educational programs that develop competence to practice are essential in sonography. Sonography is considered a user-dependent imaging modality because the quality of its examinations is heavily dependent on the expertise of the sonographer (Herbst et al, 2014;Trout, Sanchez, LadinoTorres, Pai, & Strouse, 2012). A master's program was selected for sonography education in Ireland due to this recognition of the high level of knowledge required to practice competently in this complex and rapidly evolving field.…”
Section: Introductionmentioning
confidence: 99%